Design, synthesis, and evaluation of novel racecadotril-tetrazole-amino acid derivatives as new potent analgesic agents - Mehdi Asadi; Maryam Mohammadi-Khanaposhtani; Faezeh Sadat Hosseini; Mahdi Gholami; Ahmad Reza Dehpour; Massoud Amanlou (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Although pain is one of the most common symptoms of diseases, it is often mismanaged due to limited access to painkillers and ineffectiveness, unacceptable side effects, or the possibility of abuse. However, an alternative approach to existing analgesics is to indirectly increase endogenous pain relief pathways by neprilysin (an enkephalinase) inhibitors. This enzyme breaks down and inactivates enkephalin, dynorphin, endorphins, and their derivatives. Experimental approach: In this project, a new series of racecadotril-tetrazole-amino acid derivatives 15a-l was synthesized and characterized on the basis of IR, 1H and 13C NMR, mass spectrometry, and elemental analysis. The antinociceptive activity of synthesized compounds was assessed by a hot plate, tail-flick, and formalin assays in mice. Docking was used to identify the possible interactions between neprilysin and synthesized compounds. Findings/Results: Most of the synthesized compounds showed moderate to good analgesic effects in hot plat and tail-flick test in comparison to morphine and racecadotril. Compounds 15l and 15j were the most potent compounds. The synergistic analgesic effect of compounds 15l and 15j with morphine and the antagonistic effect of naloxone on the activity of these compounds confirm that the analgesic effect of compounds 15l and 15j could be mediated through the opioidergic system. The negative and high binding energy of docking simulation of the most potent compounds in the catalytic site of neprilysin was also in good agreement with the inhibitory activity of test compounds. Conclusion and implications: Racecadotril-tetrazole-amino acid derivatives, as potential antinociceptive agents, demonstrated moderate to good antinociceptive activities comparable with morphine and higher than racecadotril.